Prime-boost, double-dose influenza vaccine immunity in COPD: a pilot observational study. Issue 2 (6th March 2023) - Anderson, Gary P.; Irving, Louis B.; Jarnicki, Andrew; Kedzierska, Katherine; Koutsakos, Marios; Kent, Stephen; Hurt, Aeron C.; Wheatley, Adam K.; Nguyen, Thi H.O.; Snape, Natale; Upham, John W.
Background: COPD patients are more susceptible to viral respiratory infections and their sequelae, and have intrinsically weaker immune responses to vaccinations against influenza and other pathogens. Prime-boost, double-dose immunisation has been suggested as a general strategy to overcome weak humoral response to vaccines, such as seasonal influenza vaccination, in susceptible populations with weak immunity. However, this strategy, which may also provide fundamental insights into the nature of weakened immunity, has not been formally studied in COPD. Methods: We conducted an open-label study of seasonal influenza vaccination in 33 vaccine-experienced COPD patients recruited from established cohorts (mean age 70 (95% CI 66.9–73.2) years; mean forced expiratory volume in 1 s/forced vital capacity ratio 53.4% (95% CI 48.0–58.8%)). Patients received two sequential standard doses of the 2018 quadrivalent influenza vaccine (15 μg haemagglutinin per strain) in a prime-boost schedule 28 days apart. We measured strain-specific antibody titres, an accepted surrogate of likely efficacy, and induction of strain-specific B-cell responses following the prime and boost immunisations. Results: Whereas priming immunisation induced the expected increase in strain-specific antibody titres, a second booster dose was strikingly ineffective at further increasing antibody titres. Similarly, priming immunisation induced strain-specific B-cells, but a second booster dose did not further enhance the B-cell response. Poor antibody responses were associated with male gender and cumulative cigarette exposure. Conclusions: Prime-boost, double-dose immunisation does not further improve influenza vaccine immunogenicity in previously vaccinated COPD patients. These findings underscore the need to design more effective vaccine strategies for COPD patients for influenza. Prime-boost, double-dose influenza immunisation does not further improve vaccine response in COPD patients, underscoring the need to design more effective vaccine strategies to overcome immune hyporesponsiveness https://bit.ly/3pd2Zas